T-lineage acute lymphoblastic leukemia and parvovirus infection in a child with neurofibromastosis-1 - Pallavi Agarwal; Shano Naseem; Neelam Varma; R K Marwaha (Wolters Kluwer Medknow Publications, 2013)
Neurofibromatosis (NF-1) patients have an increased risk of developing malignancies most commonly rhabdomyosarcomas, optic gliomas, brain tumors and non-lymphocytic leukemias. Acute lymphoblastic leukemia (ALL) has been infrequently reported in association with NF-1. We describe a rare association of NF-1, T-lineage ALL and parvovirus infection in a 12-year-old child. In addition, it is also to emphasize that a high index of suspicion should be kept for parvovirus B19 infection as a cause of bicytopenia/pancytopenia in ALL patients following induction chemotherapy.